Aberrations of m6A regulators are associated with tumorigenesis and metastasis in head and neck squamous cell carcinoma - Arumugam, Paramasivam; George, Rinku; Jayaseelan, Vijayashree Priyadharsini (Archives of oral biology, 2021)
•The m6A regulatory genes play critical roles in RNA processing via m6A modification.•We found dysregulation of m6A regulatory genes associated with tumorigenesis and metastasis in HNSCC patients.•Our findings may provide clues to identify new therapeutic targets for HNSCC. N6-Methyladenosine (m6A) is the most common RNA modification in eukaryotic mRNAs and growing evidence suggests that m6A modification and its regulators play crucial roles in human cancers. However, the role of m6A regulators and their molecular mechanisms in head and neck squamous cell carcinoma (HNSCC) remains largely unclear. We therefore assessed m6A regulatory genes alterations and their mRNAs expression in HNSCC using openly available data from The Cancer Genome Atlas (TCGA). Further, we have validated the expression level of m6A regulatory gene in HNSCC tissue samples using real-time PCR. In addition, we also analyzed the protein interaction network, and functional enrichment of m6A regulatory genes. Analysis of TCGA data revealed that m6A regulatory genes were altered in many HNSCC patients. Importantly, we found for the first time that m6A “writer” KIAA1429 (VIRMA) was frequently amplified and mutated (8 %), which contributes to the overexpression of KIAA1429 mRNA, and the overexpression of KIAA1429 could be remarkably related to cancer stages, tumor grade, and nodal metastasis (P < 0.05). In addition, the overexpression of KIAA1429 was successfully validated using HNSCC tissue samples. Our findings suggest that the genetic alterations of m6A regulatory genes are associated with tumorigenesis and metastasis in HNSCC, which may provide clues to identify new therapeutic targets for HNSCC.